MENINGKATKAN KETERAMPILAN SOSIAL ANAK MELALUI METODE BERMAIN PERAN PADA KELOMPOK B TK DWP 3 SUKODONO DAMPIT-MALANG - Umah, Fitriyatul; Nurhalimah, Evi (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2024)
The social skills of children in Kindergarten DWP 3 Sukodono Group B need to be improved. Children are still not used to communicating with other children, children are more quiet, children only want to talk when asked. The purpose of this study was to improve children's social skills through the role-playing method in Group B of Kindergarten DWP 3 Sukodono, Dampit District, Malang Regency. This study used qualitative research with the PTK or Classroom Action Research approach. Integrating the role-playing method into children's daily activities can be an effective way to help them grow and develop socially through the role-playing method. The results showed that in the pre-cycle assessment activities reached 47.5%, social skills activities through the role-playing method reached 62.27% located in cycle one at the third meeting and cycle two reached 76.36% at the third meeting exploring communication skills through the play method. The research data can be concluded that the role-playing method is effective in improving children's social skills by allowing children to enter different roles, they learn to understand the world from another person's perspective, develop empathy, and. The hope is to improve children's social skills through role-playing methods with effective learning that is centered on students.